2016
DOI: 10.1371/journal.pone.0154616
|View full text |Cite|
|
Sign up to set email alerts
|

Generation and Improvement of Effector Function of a Novel Broadly Reactive and Protective Monoclonal Antibody against Pneumococcal Surface Protein A of Streptococcus pneumoniae

Abstract: A proof-of-concept study evaluating the potential of Streptococcus pneumoniae Pneumococcal Surface Protein A (PspA) as a passive immunization target was conducted. We describe the generation and isolation of several broadly reactive mouse anti-PspA monoclonal antibodies (mAbs). MAb 140H1 displayed (i) 98% strain coverage, (ii) activity in complement deposition and opsonophagocytic killing (OPK) assays, which are thought to predict the in vivo efficacy of anti-pneumococcal mAbs, (iii) efficacy in mouse sepsis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
(55 reference statements)
0
12
1
Order By: Relevance
“…Although, some researches have indicated that PspA fragment from clade 4, especially those include all cell-surface domain, can induce high cross-reactive antibodies, our results and the conclusions from other researcher [31,32] have shown that anti-sera against PspA from clade 4 is often family-dependent and sometimes restricted to the same clade.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Although, some researches have indicated that PspA fragment from clade 4, especially those include all cell-surface domain, can induce high cross-reactive antibodies, our results and the conclusions from other researcher [31,32] have shown that anti-sera against PspA from clade 4 is often family-dependent and sometimes restricted to the same clade.…”
Section: Discussioncontrasting
confidence: 54%
“…PspA antigen is a promising vaccine candidate with protein nature against pneumococcal infections to overcome the limitations of polysaccharide-based vaccines [32]. PspA shows considerable antigenic diversity among clinical isolates and it is divided into three families with six clades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that PCV7 immunization, which contains the 19F serotype antigen, actually caused an increase in pneumococcal infections by the closely related 19A serotype ( 16 ). Globally, this is of particular concern when considering the development of a universal vaccine, as it is now clear that the prevalence of certain serotypes differs greatly between age, geographic region, and ethnicity ( 3 , 17 , 18 ). PPV23 encompasses the most pneumococcal serotypes of the commercially available vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…PspA has been of recent interest as a potential vaccine candidate due to its location on the cell surface of all 95 strains of S. pneumoniae currently known and its critical role in pneumococcal pathogenesis ( 3 , 23 , 24 ). Anti-PspA antibodies to clades 1 and 2 of PspA have been shown to be cross-protective against S. pneumoniae strains encompassing all six clades of PspA, and provide protection when passively transferred to naïve mice as a therapeutic intervention following septic S. pneumoniae challenge ( 17 , 25 27 ). The ability to provide protection across many serotypes of S. pneumoniae using only two clades of PspA allows for the design of a broadly cross-protective vaccine when compared to vaccines containing numerous capsular polysaccharides.…”
Section: Introductionmentioning
confidence: 99%